(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present study examined the verbal behavior of a person diagnosed with schizophrenia Participant consisted of a a, female, 41 years old, married, with several admissions to psychiatric institutions, and member of the evangelical community.. Four controlling purposes, multiple conditions (with four main conditions: attention, demand, alone and control) was employed. The attention condition was subdivided into four subconditions: attention-question attention connivance, attention-reproach and attention-temple.Alternate treatment design was used for the treatment. The results confirmed that the social care exerted control over the participant’s inappropriate speaking. The results also showed that in the attention-temple condition and reprimand attention the highest number of IF was recorded. In all conditions, a functional analysis of the verbal behavior of the participant was perfomed.